Expert System Disease Diagnosis and Drug Relation Amor Pharmacy - Ilyas Ilyas (Institute of Computer Science (IOCS), 2020)
The development of information and communication technology today has a major influence on various aspects of life, even human behavior and activities now depend a lot on information and communication technology. One example is the use of expert system-based technology. The development of expert system-based applications has been in great demand since 1950, with a fairly wide coverage area. Expert systems in organizations are aimed at adding value, increasing productivity and managerial areas that can draw conclusions quickly. In this study an application was developed